INVESTIGASI TINGKAT KETERLIBATAN MATEMATIKA SISWA MELALUI ANALISIS RANCANGAN PELAKSANAAN PEMBELAJARAN ELPSA DAN IMPLEMENTASINYA DI KELAS - Febrilia, Baiq Rika Ayu; Patahuddin, Sitti Maesuri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2019)
The quality of mathematics learning is reflected by the quality of mathematical engagement during the enacted lesson, while the enacted lesson is determined by the intended lesson. Therefore, having a well-developed lesson plan is critical to achieve learning objectives. This study aims to explored students‟ mathematical engagement based on two triangle lesson plans and their implementation to 7th graders students. The research methods was used is qualitative descriptive. This research involved one male teacher and 24 students. Students‟ mathematical engagement was analysed through the students‟ words and actions using an adapted Watson‟s analytical tool. The results of this analysis indicate that there were 24 out of 38 indicators of mathematical engagement intended in the lesson plans and this result also were aligned with students‟ mathematical engagement that occurred in the classroom. The frequency of occurrence of the indicators were varied, some aspects were relatively high, such as using prior knowledge and identifying mathematical characteristics, while some other aspects were quite low, such as clarifying and associating ideas. This study shows that the analytical tool used in the analysis allowed us to focus attention on activities that are mathematical. DOI: 10.22342/jpm.13.1.6326.55-72